2015
DOI: 10.1021/acs.jafc.5b04341
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Lipid Peroxidation of Unsaturated Fatty Acids in the Retina and the Inhibitory Effects of Blueberry Polyphenols

Abstract: The lipid peroxidation of unsaturated fatty acids (UFAs) in the retina not only threatens visual cells but also affects the physiological health of the retina. In this work, the potential damages caused by daily visible light exposure on retinal UFAs were evaluated via a simulated in vitro model. At the same time, the benefits of dietary supplementation of blueberries to the eyes were also assessed. After prolonged light exposure, lipid peroxidation occurred for both docosahexaenoic and arachidonic acids (DHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Anthocyanins in berries contribute to eye health, especially cyanidin-3-glucoside in blueberry, is a preventive functional food for the prevention of retinal diseases [ 47 ]. Blueberry polyphenols have the retinal protective activity against light-induced retinal injury in eyes [ 48 ] (see Table 1 ).…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Anthocyanins in berries contribute to eye health, especially cyanidin-3-glucoside in blueberry, is a preventive functional food for the prevention of retinal diseases [ 47 ]. Blueberry polyphenols have the retinal protective activity against light-induced retinal injury in eyes [ 48 ] (see Table 1 ).…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Blueberries are famous for their wide range of health benefits, including ameliorating diabetes, attenuating vascular problems, maintaining endothelial function, and preventing retinal diseases [ 15 ]. Many scientists have reported that blueberry components such as anthocyanins, polyphenols, and pterostilbene can protect corneal epithelial cells against light-induced retinal injury via antioxidative, antiangiogenic, and antiaging effects in vitro, and the bioactivity of blueberries in improving vision has been confirmed in vivo [ 13 , 16 , 17 ]. However, the function of blueberry anthocyanins on human retinal capillary endothelial cells (HRCECs) is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…4-HNE is derived from n-6 PUFAs, like linoleic acid and arachidonic acid, while 4-HHE is formed from n-3 PUFAs such as docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and linolenic acid [ 12 ]. These three major unsaturated fatty acids reached about 50%, 10%, and 8% of the total fatty acids, respectively, in human retina [ 13 ]. Due to the structure similarities of 4-HNE and 4-HHE, these two aldehydes showed a number of cytotoxic effects, including inhibition on selective enzyme activity, induction on cell cycle arrest, and cell apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%